Prediksi Pola Penjualan Produk Herbal Menggunakan Algoritma FP-Growth - Supinah; Rezi Elsya Putra; Mohd. Iqbal (SEULANGA SYSTEM PUBLISHER, 2022)
The pattern of sales is a necessity in a business, in increasing sales strategies setting patterns will help the business progress. The pattern of selling these herbal products can increase sales and convenience for sellers and buyers compared to manual settings. Setting the layout of herbal products can facilitate customers in the selection of interrelated products. Continuous product prediction can be easily recognized by the seller. The sales pattern prediction in this study uses transaction data as many as 33 sales transactions in less than the last three months originating from the sale of Batam HNI Bussiness Center 2 herbal products. Based on sales analysis using the FP-Growth algorithm can predict the pattern of sales of herbal products for the future. Furthermore, transaction data is processed using Rapidminer Studio version 9.0 software with 68 transaction data, then from the results of testing on this method the percentage of success is 80%. Comparison uses 10 sales data samples. Opportunities to choose interrelated products greatly help customers when shopping and predict future customer needs. The sales pattern prediction has helped to overcome the instability of herbal product supplies at Batam's HNI Bussiness Center 2.